Improving the Studentsâ€™ Ability in Using the Expression of â€œAsking for and Giving Information by Using Chit Chat Strategy at the Seventh Grade of SMPN I Semanding - Maskuri, Moch (JET ADI BUANA, 2016)
This research aims to describe the process of improving the studentsâ€™ competence in expressing â€œasking for and giving information and to know the studentsâ€™ achievement in expressing â€œâ€asking for and giving information at the seventh grade of SMP N I Semanding, Tuban. This research is carried by using classroom action research. The subject of the study is class A of seventh grade of SMP N I Semanding, Tuban. The writer only takes class A that consists of 30 students. In conducting the research, the writer uses the procedure of classroom action research. They are planning, Acting, Observing and Reflecting. In collecting the data the writer uses the following procedures: Conducting the observation and giving test. In analyzing the data the writer uses the procedure of collecting data. they are describing the process of improving the studentsâ€™ competence, correcting the students test, and describing the studentsâ€™ achievement. Based on the research result, it is found that the process of improving the studentsâ€™ competence in expressingâ€asking for and giving informationâ€ is done in two cycles. In cycle 1, the students had not been able to achieve â€œKKMâ€ (kriteria kelayakan minimal). Then the writer continouses the second cycle. Finally all students Achieved â€œKKMâ€. Based on the result of the test, it is found that some of the students had not been able to achive â€œKKMâ€ at first cycle. Then, the writer did the second cycle. Based on the test result of second cycle, it is found that all students had achieved more than 65. It is the score of â€œKKMâ€. The varage score is 73,5. It is categorized as good. It can be concluded that chit-chat game can improve the studentsâ€™ ability of the seventh grade of SMP N I Semanding, Tuban in expressing â€œasking for and giving informationâ€